A systematic review of irrigation development and agricultural water management in Mali - Mabhaudhi, T.; Dirwai, Tinashe Lindel; Taguta, C.; Kanda, E. K.; Nhamo, L.; Cofie, Olufunke O. (Springer, 2025)
Rain-fed and irrigated agriculture are key to economic growth, job creation, food security, and livelihoods across Africa. Agriculture in Mali is mainly rain-fed and thus vulnerable to the country’s fluctuating climate, which undermines crop production and productivity. The PRISMA protocol and SPIDER framework were used to systematically review Mali’s irrigation development and agricultural water management. Mali invested in irrigated agriculture across scales to decouple agriculture from unreliable rainfall, but the potential for expansion still exists. The Malian government also developed several policies to create an enabling environment that promotes agricultural water management (AWM). Farmers employ various agricultural water management practices to control and conserve water and soil. In line with the African Union irrigation development and agricultural water management (AU-IDAWM) framework, there exists operationalization challenges in Mali. These challenges include weak implementation of policies by authorities and lack of awareness among farmers, to mention a few. Farmers lack access to inputs, technology, extension services and credit. The government lacks the financial capacity to rehabilitate irrigation schemes such as Office du Niger, wherein it politically allocated land to foreign large-scale investors without the involvement of the farmers and the management agency, and this may affect the sustainability of irrigated agriculture. Wastewater irrigation suffers from non-recognition, lack of support from all spheres, and risks to human health and the environment. Thus, the government must revamp policy implementation and utilize alternative financing models to rehabilitate irrigation infrastructure, such as private–public partnerships (PPPs). There is a need to minimize political interference in the allocation of agricultural land in the Office du Niger. Subsidies are needed to support farmers with technology and inputs for irrigation and AWM. Farmers, extension workers, and equipment suppliers must be trained to build their capacity. Wastewater irrigation contributes to food supply, income generation, and livelihoods in peri-urban and urban areas. Thus, this practice must be formalized and supported by policies, guidelines, regulations, standards, and technologies for on-site water treatment and safer irrigation practices.